THE EFFECT OF PRODUCT QUALITY AND BRAND IMAGE ON THE PURCHASE DECISION OF MS.GLOW SKINCARE PRODUCTS THROUGH PURCHASE INTEREST AS A MEDIATION VARIABLE IN USERS OF MS.GLOW SKINCARE PRODUCTS IN TERNATE - Fadila Ahmad; Ida Hidayanti; Johan Fahri (IAIN Surakarta, 2022)
This study aims to determine the effect of product quality and brand image on purchasing decisions through buying interest. This research was a quantitative research. The population in this study were consumers using skincare ms.glow products in Ternate with the sampling method, namely Non-Probability Sampling with a purposive sampling approach. The data analysis technique was path modeling analysis using Smart Partial Least Square (PLS) version 3 as a statistical test tool. The results of this study indicate that product quality has a significant effect on purchasing decisions, brand image has no significant effect on purchasing decisions, product quality has a significant effect on buying interest, brand image has a significant effect on buying interest, buying interest has a significant effect on purchasing decisions, product quality has a significant effect on purchasing decisions through buying interest, and brand image has a significant effect on purchasing decisions through buying interest.